High Yielding Soybean: Genetic Gain and Nitrogen Limitation - O. A. Ortez; F. Salvagiotti; J. M. Enrico; E. A. Adee; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2018)
The United States and Argentina account for more than 50% of the global soybean production. Closing yield gaps (actual on-farm yield vs. genetic yield potential) would require an improvement in the use of the available resources. Overall, 50-60% of soybean nitrogen (N) demand is usually met by the biological nitrogen fixation (BNF) process. A scientific knowledge gap still exists related to the ability of the BNF process to satisfy soybean N demand at varying yield levels. The overall objective of this project is to study the contribution of N via utilization of varying N strategies under historical and modern soybean genotypes. Two field experiments were conducted during the 2016-2017 growing seasons: Rossville, KS (US) and Oliveros, Santa Fe (ARG). This report focuses on the 2016 results. Twenty-one historical and modern soybean genotypes were utilized with release decades between 1980s and 2010s. All were inoculated and tested under three N management strategies: S1, non-N applied; S2, all N provided by fertilizer; and S3, late-N applied. The genetic improvement of soybean yield from the 1980s to 2010s was an overall increase of 30%, averaging results from US and ARG. Seed N content (N exported in seed) followed a similar trend for yield, while N concentration in seed was decreased as yields increased. Regarding N management for genotypes from all release decades, S2 (all N provided by fertilizer) generated up to a 20% increase in yields in the US and 5% in ARG. These results suggest that high yielding soybeans could be limited by N under specific growing conditions to express the yield potential.
Keywords: soybean genetic gain; K-State soybean research; high yielding soybean; soybean nitrogen limitation